Inflammatory mechanisms in the lung - B Moldoveanu; P Otmishi; P Jani; J Walker; X Sarmiento; et al (Dove Medical Press, 2008)
B Moldoveanu1, P Otmishi1, P Jani1, J Walker1,2, X Sarmiento3, J Guardiola1, M Saad1, Jerry Yu11Department of Medicine, University of Louisville, Louisville, KY, USA, 40292; 2Department of Respiratory Therapy, Bellarmine University, Louisville, KY, USA, 40205; 3Intensive Care Medicine Service, University Hospital Germans Trias i Pujol, Badalona, Spain 08916Abstract: Inflammation is the body’s response to insults, which include infection, trauma, and hypersensitivity. The inflammatory response is complex and involves a variety of mechanisms to defend against pathogens and repair tissue. In the lung, inflammation is usually caused by pathogens or by exposure to toxins, pollutants, irritants, and allergens. During inflammation, numerous types of inflammatory cells are activated. Each releases cytokines and mediators to modify activities of other inflammatory cells. Orchestration of these cells and molecules leads to progression of inflammation. Clinically, acute inflammation is seen in pneumonia and acute respiratory distress syndrome (ARDS), whereas chronic inflammation is represented by asthma and chronic obstructive pulmonary disease (COPD). Because the lung is a vital organ for gas exchange, excessive inflammation can be life threatening. Because the lung is constantly exposed to harmful pathogens, an immediate and intense defense action (mainly inflammation) is required to eliminate the invaders as early as possible. A delicate balance between inflammation and anti-inflammation is essential for lung homeostasis. A full understanding of the underlying mechanisms is vital in the treatment of patients with lung inflammation. This review focuses on cellular and molecular aspects of lung inflammation during acute and chronic inflammatory states.Keywords: inflammation, lung, inflammatory mediators, cytokines